Challenges facing African agriculture - Babu, Suresh Chandra; Anandajayasekeram, P.; Rukuni, M. (CAB International, 2007)
At independence in 1960, Africa was a modest food exporter while Asia was engulfed in a food crisis. The Green Revolution boosted food production in Asia and the global food problem shifted to Africa. However, science and technology have been promoted on an ad hoc basis in Africa's 45 years of independence. This chapter analyses why the Asian Green Revolution failed to take root in Africa, and why the average African grain yield has been flat since 1960. The chapter shows that the rate of return has been high on investments in research for a few commodities, such as hybrid maize, rice and flowers. However, most countries in Africa have a weak scientific and institutional foundation for transforming agriculture. Long-term investments are required to build the scientific and institutional foundation for a modern agriculture. This is a tall order, but this is what the USA accomplished from 1860 to 1912, what Japan did from 1868 to 1914 and what many countries in Asia and Latin America have accomplished over the past 40 years. The challenge now is to mobilize African political leaders and donors to make long-term accretionary (step by step) investments in science and technology that will boost cereal yields, increase agricultural productivity and drive down real (inflation adjusted) food prices. This is a proven way to reduce urban poverty and the poverty of rural families who are net food buyers. This book brings together empirical evidence from 20 studies on the impact of investments in agricultural research and food security in Africa. Information on the returns to investments in research can help countries in setting priorities for agricultural research. The purpose of this chapter is to highlight the emerging issues, challenges and constraints on African agriculture that beg serious attention from the policy makers. It enumerates a broad set of food security challenges facing African agriculture. Finally, it identifies successes in African agriculture and recent efforts aimed at scaling-up the successes.